2016
DOI: 10.1016/j.conbuildmat.2016.02.219
|View full text |Cite
|
Sign up to set email alerts
|

Axial load-axial deformation behaviour of circular concrete columns reinforced with GFRP bars and helices

Abstract: Fibre Reinforced Polymer (FRP) bars has attracted a significant amount of research attention in the last three decades to overcome the problems associated with the corrosion of steel reinforcing bars in reinforced concrete members. A limited number of studies, however, have investigated the behaviour of concrete columns reinforced with FRP bars. Also, available design standards either ignore the contribution of or do not recommend the use of GFRP bars in compression members. This study reports the results of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 118 publications
(53 citation statements)
references
References 36 publications
2
50
0
Order By: Relevance
“…Providing spirals activated the lateral confinement at the load-deformation part after 1 , so that columns A-50-26.8, A-100-26.8, and A-150-26.8 retained most of the applied load with only a 1%, 10%, and 7% reduction in 1 , respectively. Karim, et al (2016) made similar observations. After that point, the lateral expansion of the cracking concrete was restricted by the lateral spirals, allowing the column to continue resisting the applied load at the post-loading stage at which point the concrete cover no longer makes a load contribution.…”
Section: Load-deformation Behaviorsupporting
confidence: 60%
See 1 more Smart Citation
“…Providing spirals activated the lateral confinement at the load-deformation part after 1 , so that columns A-50-26.8, A-100-26.8, and A-150-26.8 retained most of the applied load with only a 1%, 10%, and 7% reduction in 1 , respectively. Karim, et al (2016) made similar observations. After that point, the lateral expansion of the cracking concrete was restricted by the lateral spirals, allowing the column to continue resisting the applied load at the post-loading stage at which point the concrete cover no longer makes a load contribution.…”
Section: Load-deformation Behaviorsupporting
confidence: 60%
“…6]. Equation (4) was adopted from Karim, et al (2016), who evaluated the lateral confinement of the solid GFRP-reinforced columns, and Eq. (6) from Mander, et al (1988) to reduce the lateral-stress effectiveness caused by the discontinuous lateral confinement.…”
Section: Design-load Capacitymentioning
confidence: 99%
“…Muhammad N.S. Hadi et al [8] suggested following formula in which the confinement effect was taken into account:…”
Section:  mentioning
confidence: 99%
“…Table 4 summarizes the test results of all concrete columns. In this study, the ductility of the specimens was calculated as the ratio of the axial deformation at the ultimate load to the axial deformation at the first peak load [35][36][37]. For the specimens without a clear first peak load, axial deformation at the transition point between the first and second ascending parts was taken [36,37].…”
Section: Axial Load-axial Deformation Behaviourmentioning
confidence: 99%